(untitled) (Eurasian Journal of Philology Science and Education, 2025)
Through linguistic research it becomes possible to reveal the ethnocultural content of the fundamental components and concepts that form system of values of the spiritual space of one particular ethnos. The study of language in close connection with man, animals (birds’ flight) and the world is considered as dominant direction of the anthropocentric paradigm. The predominant use of ornithonyms in the poetry of zhyrau poets in the historical culture of the ethnos allows us to see the role played by lifestyle, culture, geographical location, traditions of the people in the process of formation of national image of the world. The study of ornithonymic components used in the poetry of poets-zhyrau allows us to comprehensively learn not only the cultural and cognitive attitude of representatives of ethnic community to the world of birds that connects heaven and earth, but also the content of folk knowledge in the field of analogy, zoology, ornithology and botany. Ornithonyms in the poetry of zhyrauls serve as a basis for ethno-cultural research, which considers the national specificity of the world of birds in the historical layer of spiritual treasury in the relationship with language. Ornithonymic components in the poetry of zhyrau poets are considered as a special object in the material of the research, and it comprehensively studies cultural-cognitive, linguistic, evaluative and ethnic features of ornithonyms in the national culture from the theoretical and practical point of view.The linguistic representation of the world of birds in the poetry of zhyrau poets, place of ornithonyms in the national culture, semantics of bird names, their ethnographic nature, linguocultural semantic code are considered from the linguistic point of view. Studying of ornithonymic components of the research material is aimed at an attempt to understand the ethnocultural nature of national identity from a linguistic point of view. Such studies substantiate the fact that ornithonims are a national-cultural value, a part of the world formed in the collective consciousness of an ethnos. The axiological, symbolic, archetypal and ethnographic significance of ornithonymic components in historical-artistic texts is analysed on the basis of linguocultural principles of studying the ‘linguistic image of the bird world’ of the native speaker’s ethnos. Many methods of linguocultural analysis and component analysis are widely used in studying linguistic representation of ornithonymic components in zhyraus’ poetry. The representatives of the ethnos were familiar with all parts of nature (ornithonyms). The figurative, semantic and value characteristics of using ornithonymic components in zhyraus’ poetry as a model of the process of harmonisation of ethnos culture with nature are scientifically determined. Key words: zhyrau poets, artistic text, poetry, ornithonym, component, ethnicity, spirituality, culture.